Basis of melanin distribution in the human skin epidermis. (2nd November 2018) - Joly‐Tonetti, N.; Wibawa, J.I.D.; Bell, M.; Tobin, D.J.
Summary: The skin is comprised of three core layers, and the outermost layer is the epidermis. The epidermis is itself comprised of four further layers: the lowest being the basal cell layer, which is where skin cells called melanocytes continuously make the skin's pigment, melanin. 90 per cent of cells in the epidermis are keratinocytes, which multiply and migrate upwards from the basal cell layer up to the skin's surface, and melanin is carried by these keratinocytes. Scientists looking at skin's total melanin have found that most melanin remains in the basal cell layer with only a little moving towards the skin's surface, but the reasons for this have been unclear. It has been thought that perhaps melanin degrades as the keratinocytes migrate upwards out of the basal layer. This study from the UK challenges this belief. The researchers tested skin of 11 Caucasian women and focuses on what happens to melanin in a keratinocyte cell that divides (creating two new cells). One of the new cells is designed to stay in the basal cell layer, while the other is designed to travel upwards. They found that the vast majority of melanin was retained within the cell that stays in the basal layer but by contrast, the second cell destined to leave the basal layer had very little melanin. The researchers also found that this distribution can be switched when there is stress to skin tissue, such as tissue regeneration or wound‐healing, when both new cells now receive equal amounts of melanin. This research provides important information to help further research into pigmentation disorders of the skin. Abstract : Linked Article: Joly‐Tonetti et al. Br J Dermatol 2018; 179 :1115–1126